The measurement of the wear of tie rod end components - Wozniak, Marek (Strojniški vestnik, 2022)
This study aimed to determine the wear intensity of the bearing mating with the ball stud in the tie rod end. The course of the vehicle driving during the period between repairs of the steering assembly was assumed. The modelled scheme of cornering was assumed to be close to the real one. The model of steering mechanism allowing determination of the load of the stud of the tie rod end as a function of the steering angle was elaborated and presented. The model of the ball stud was realized and described. The values of wear intensity for components were calculated and presented.
Keywords: finite element method; končniki; kontaktni tlak; mast; metoda končnih elementov; sistem krmilnega mehanizma; steering mechanism system; stisnjen film; stopnja obrabe; tie rod ends; wear degree